Antitumor Activity of a Mesenchymal Stem Cell Line Stably Secreting a Tumor-Targeted TNF-Related Apoptosis-Inducing Ligand Fusion Protein - Marini, Irene; Siegemund, Martin; Hutt, Meike; Kontermann, Roland E.; Pfizenmaier, Klaus (Frontiers in Immunology, 2017)
Mesenchymal stem cells (MSCs) are currently exploited as gene delivery systems for transient in situ expression of cancer therapeutics. As an alternative to the prevailing viral expression, we here describe a murine MSC line stably expressing a therapeutic protein for up to 42 passages, yet fully maintaining mesenchymal stem cell features. Because of superior anti-tumoral activity of hexavalent TRAIL formats and the advantage of a tumor-targeted action, we choose expression of a dimeric EGFR-specific diabody single-chain TRAIL (Db-scTRAIL) as a model. The bioactivity of Db-scTRAIL produced from an isolated clone (MSC.TRAIL) was revealed from cell death induction in Colo205 cells treated with either culture supernatants from or co-cultured with MSC.TRAIL. In vivo, therapeutic activity of MSC.TRAIL was shown upon peritumoral injection in a Colo205 xenograft tumor model. Best anti-tumor activity in vitro and in vivo was observed upon combined treatment of MSC.TRAIL with bortezomib. Importantly, in vivo combination treatment did not cause apparent hepatotoxicity, weight loss or behavioral changes. The development of well characterized stocks of stable drug-producing human MSC lines has the potential to establish standardized protocols of cell based therapy broadly applicable in cancer treatment.